Precursors of Warehousing Efficiency: An Empirical Study and Evaluation within an Industrialized Hub of a Developing Economy, Ghana - Appiah, Alexander; Teye, Richard; Asare, John (International Journal of Supply Chain Management, 2018)
Warehousing make up a significant proportion of companies’ logistics costs. As a result the study was carried out to determine the mediating role of transportation on the relationship between inventory management and warehousing efficiency. We present an ‘elegant’ warehouse efficacy mediating model rooted in the theory of working capital management (WCM) and the “value of added role of logistics” using data from 216 firms who operate a warehouse at Tema - the industrial hub of developing economy, Ghana. Confirmatory factor analysis (CFA) was run in LISREL 8.8. Hierarchical regression and Hayes (2013) process Macro for SPSS was used to estimate four hypothesized paths from a proposed theoretical framework. Findings from the study suggest that robust transportation and inventory management decisions independently drives firms to be efficient in their warehousing operations. The study’s findings further suggest that achieving transport objectives is also reliant on inventory management. However, dwelling on a superior mediation model, a firm’s ability to manage inventory in achieving efficiency in their warehousing operations is driven through their transportation inititaives. We discuss several managerial and theoretical implications as well as provide directions for future research.